Psychological Well-Being Korban Kekerasan Dalam Pacaran: Adakah Peranan Forgiveness? - Prasetyo, Andry Henry; Meiyuntariningsih, Tatik; Ramadhani, Hetti Sari (JIWA: Jurnal Psikologi Indonesia, 2023)
Psychological well-beingis self-assessment or self-evaluation resulting from the experiences and ambitions of an individual's life. Individuals have a positive attitude towards themselves and others, make their own decisions, regulate their behavior, have meaningful life goals and are able to fulfill their potential and are able to manage their environment according to their needs. The purpose of this study was to determine the relationship between forgiveness and psychological well-being in victims of dating violence. The research design uses quantitative methods to achieve research objectives. The subjects of this study were victims of dating violence in Surabaya, totaling 95 women. The measuring instrument uses forgiveness and psychological well-being scales, dating violence to find subject criteria. The data analysis technique uses the Spearman Brown correlation test. The results show that there is a significant positive relationship between forgiveness and psychological well-being in victims of dating violence. The hypothesis that says there is a relationship between forgiveness and psychological well-being in victims of dating violence is accepted. Psychological well-being adalah penilaian atau evaluasi diri yang dihasilkan dari pengalaman dan ambisi hidup individu. Individu memiliki sikap positif terhadap dirinya sendiri dan orang lain, membuat keputusan sendiri, mengatur perilakunya, memiliki tujuan hidup yang bermakna dan mampu memenuhi potensi dirinya serta mampu mengelola lingkungannya sesuai dengan kebutuhannya. Tujuan dari penelitian ini untuk mengetahui hubungan antara forgiveness dengan psychological well-being pada korban kekerasan dalam pacaran. Desain penelitian menggunakan metode kuantitatif untuk mencapai tujuan penelitian. Subjek penelitian ini adalah korban kekerasan dalam pacaran di Surabaya yang berjumlah 95 perempuan. Instrumen alat ukur menggunakan skala forgiveness dan psychological well-being, kekerasan dalam pacaran untuk mencari kriteria subjek. Teknik analisis data menggunakan uji korelasi Spearman Brown. Hasil terdapat hubungan positif yang signifikan antara forgiveness dengan psychological well-being pada korban kekerasan dalam pacaran. Hipotesis yang berbunyi ada hubungan antara forgiveness dengan psychological well-being pada korban kekerasan dalam pacaran diterima.